Tacrolimus (FK506) causes disease aggravation in models for inherited peripheral myelinopathies - Chi Wang Ip; Antje Kroner; Bianca Kohl; Carsten Wessig; Rudolf Martini (Neurobiology of Disease, 2009)
Mice hetero- or homozygously deficient for myelin protein zero (P0+/−, P0−/− mice) are models for distinct forms of inherited de- or dysmyelinating neuropathies, respectively. P0+/− mice show a demyelinating neuropathy with a pathogenetic implication of CD8+ T-lymphocytes and macrophages, while P0−/− mice show dysmyelination with axonal loss. It was, therefore, of interest to treat both mutants with FK506 (Tacrolimus), an agent with immunosuppressive and neuroprotective properties. Treatment of P0+/− mice led to an aggravation of demyelination, without affecting nervous CD8+ T-lymphocytes, but reducing splenic CD4+ cells. Treatment of P0-/− mice resulted in a substantial increase of the dysmyelination-related axon loss. Treatment of wildtype mice did not cause pathological changes in peripheral nerves.Our study shows that FK506 may not be suitable for the treatment of the human nerve disorders. Furthermore, when used as an immunosuppressant, the drug may generate detrimental neurological side effects in patients with an additional hereditary neuropathy.